2016
DOI: 10.1155/2016/3216523
|View full text |Cite
|
Sign up to set email alerts
|

Selective Sensing of Tyrosine Phosphorylation in Peptides Using Terbium(III) Complexes

Abstract: Phosphorylation of tyrosine residues in proteins, as well as their dephosphorylation, is closely related to various diseases. However, this phosphorylation is usually accompanied by more abundant phosphorylation of serine and threonine residues in the proteins and covers only 0.05% of the total phosphorylation. Accordingly, highly selective detection of phosphorylated tyrosine in proteins is an urgent subject. In this review, recent developments in this field are described. Monomeric and binuclear TbIII comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 139 publications
(86 reference statements)
0
10
0
Order By: Relevance
“…LanthaScreen assays measure the fluorescence energy transfer (FRET) from a phospho-tyrosine antibody labelled with a donor fluorophore to the acceptor fluorescent dye that is conjugated to a substrate peptide. The method uses the exceptionally long fluorescence life time of lanthanide ions (europium or terbium), which allows to delay the measurement of donor and acceptor emission until background fluorescence from other potentially interfering compounds has decayed (Sumaoka, Akiba, & Komiyama, 2016;Carlson, Robers, Vogel, & Machleidt, 2009).…”
Section: In-vitro Kinase Activity Assaysmentioning
confidence: 99%
“…LanthaScreen assays measure the fluorescence energy transfer (FRET) from a phospho-tyrosine antibody labelled with a donor fluorophore to the acceptor fluorescent dye that is conjugated to a substrate peptide. The method uses the exceptionally long fluorescence life time of lanthanide ions (europium or terbium), which allows to delay the measurement of donor and acceptor emission until background fluorescence from other potentially interfering compounds has decayed (Sumaoka, Akiba, & Komiyama, 2016;Carlson, Robers, Vogel, & Machleidt, 2009).…”
Section: In-vitro Kinase Activity Assaysmentioning
confidence: 99%
“…Recently, Sumaoka and co-workers demonstrated that lanthanide ions and their complexes such as Terbium (III) complexes show high selectivity to phosphotyrosine (pTyr) [42]. Another similar study was reported by Hussain et al, who fabricated diamond-lanthanum oxide and diamond-samarium oxide nanocomposites and applied them to selectively capture phosphorylated peptides from β-casein and BSA.…”
Section: Phosphoprotein/phosphopeptide Enrichment or Phosphate Recmentioning
confidence: 93%
“…Kinase-catalyzed phosphorylation of fluorescent peptides promotes their binding to metal-coated nanoparticles, which decreases their mobility and enhances measurable fluorescence polarization (Lea and Simeonov, 2011;Sportsman et al, 2004). TbIII complexes, in which phosphotyrosine induces fluorescence emission (Wang et al, 2015a), may be used to evaluate protein tyrosine kinase activity (Akiba et al, 2015;Sumaoka et al, 2016). Fluorescence polarization methods also can be useful for drug screening [reviewed in (Hall et al, 2016)].…”
Section: Kinasesmentioning
confidence: 99%